Effects of Surgical Site Infection Surveillance Focused on Feedback in Colorectal Surgery - MORIKANE, Keita; DAITO, Yoshiko (Japanese Journal of Infection Prevention and Control, 2023)
Feedback-focused surgical site infection (SSI) surveillance was conducted in 508 patients undergoing colorectal surgery. Infection control team provided the results and analyses of surveillance data to surgeons, operating room nurses, and surgical ward nurses as an intervention to prevent SSI. We investigated the effect of our surveillance on the control of SSI. The study period was from January 2013 to December 2020 and was divided into three periods: the intervention period from January to December 2015, the early period from January 2013 to December 2014, and the late period from January 2016 to December 2020. In the feedback, we tried to provide opportunities for the subjects to voluntarily exchange opinions about SSI prevention measures. The mean incidence of SSI showed a statistically significant decrease, from 30.2% in the early period to 13.4% in the late period (P<0.001). The results of a logistic regression analysis of risk factors for SSI development revealed that male gender (odds ratio [OR], 2.30; 95% confidence interval [CI], 1.320-3.980; P<0.01) was an independent risk factor for SSI development and that endoscopy (OR, 0.39; 95% CI, 0.233-0.665; P<0.001) and the late period with feedback (OR, 0.51; 95% CI, 0.299-0.853; P=0.01) were independent protective factors for SSI development. This suggests that feedback-focused SSI surveillance reduces the incidence of SSI.